Strategi Media Relations Dinas Komunikasi dan Informatika Kabupaten Luwu Timur dalam Peningkatan Sarana Informasi Publik - Dimas Prayogi; Agung Prawijaya (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2022)
This research aims to find out the strategy used by the Communication and Informatics Office of East Luwu in improving public information facilities and the supporting and inhibiting factors in these efforts. The method used in solving this problem is the Descriptive Qualitative Method. Data Collection Techniques are used through observation, interviews, and documentation. The result of the research is the strategy used in improving the facilities using cooperation with media called Diskominfo Media Partner which consists of 20 online media and 9 print media. Therefore. It also utilizes social media in disseminating information since it is society’s most used platform. The Communication and Informatics Office can give the service optimally to the public. The public can also get benefits such as information and other good services. Based on the results, it can be concluded that there are still obstacles to implementing the established strategy, namely the lack of human resources, the lack of facilities and infrastructure, and the location factor in spreading information.